Phylogeny, biogeography and divergence times in Passiflora (Passifloraceae) - Valéria C. Muschner (Genetics and Molecular Biology, 2012)
As part of a long-term investigation on the evolution of Passiflora L., we investigated the divergence ages of the genus and diversification of its subgenera, relating them with biogeographical and/or historical events, and other characteristics of this taxon. The main aim of the present work was to evaluate the biogeographic distribution of this genus to better understand its evolutionary history. This is the first time that representatives from South American and Old World Passifloraceae genera have been studied as a group comprising a total of 106 widely distributed species, with representative samples of the four suggested subgenera. Seven DNA regions were studied, comprising 7,431 nucleotides from plastidial, mitochondrial and nuclear genomes. Divergence time estimates were obtained by using a Bayesian Markov Chain Monte Carlo method and a random local clock model for each partition. Three major subgenera have been shown to be monophyletic and here we are proposing to include another subgenus in the Passiflora infrageneric classification. In general, divergence among the four subgenera in Passiflora is very ancient, ranging from ~32 to ~38 Mya, and Passifloraceae seems to follow a biogeographic scenario proposed for several plant groups, originating in Africa, crossing to Europe/Asia and arriving in the New World by way of land bridges. Our results indicated that Passiflora ancestors arrived in Central America and diversified quickly from there, with many long distance dispersion events.